TINJAUAN HUKUM ISLAM TERHADAP FUNGSI BALAI HARTA PENINGGALAN DALAM MENGURUS HARTA KEKAYAAN ORANG YANG TIDAK HADIR - Yuniarlin, Prihati; Heriyani, Endang (Jurnal Media Hukum, 2018)
People who are absent do not lose their status as legal subjects who have rights and obligations. For this reason, it is necessary to protect both the interests and property. The purpose of this study was to find out whether the Heritage Hall had fulfilled its function in managing the assets of people who were not present. This research is a normative legal research with a conceptual approach (conceptual approach) and a law approach. The informant in this study is an Islamic Civil Law Expert. The study is showed 3 results. First, the Heritage Property has fulfilled its function in managing the assets of people who absent. Second, the existence of the Institution of Treasury Hall can provide legal protection for the assets of people who absent. Third, the function of the Treasure House in managing the assets of people who absent can be said to be in accordance with Islamic law. Although the task of managing or managing the assets of people who absent is different, in Islamic Law the institution authorized to take care of the assets of people who absent is the Temporary Zakat Agency according to the Civil Code, the management of assets that are not present is the Heritage Hall . However, the essence is same, both the Amil Zakat Institution and BHP in principle represent the State in managing the assets of people who absent.